Jewish bodylore: feminist and queer ethnographies of folk practices - Milligan, Amy K. (Studies in folklore and ethnology, 2019)
Introduction: Jews, gender, and bodylore -- Chapter 1: The subversive Jewish feminist body: creating spaces of protest through embodiment in synagogue life -- Chapter 2: Renewing her body: engaging Jewish women's bodies in synagogue life -- Chapter 3: Rebellious hair: Jewish feminist reinterpretations of the Orthodox Jewish ritual of Upsherin -- Chapter 4: The Rose Winkel: Jewish navigation of the reappropriation of a Nazi symbol by LGBTQ young adults -- Chapter 5: Queerly stitched: religious garb and LGBTQ Jewish pride symbols -- Conclusion: Applications of Jewish feminist bodylore.